Energetics of kayaking at submaximal and maximal speeds - Zamparo, P.; Capelli, C.; Guerrini, G. (European Journal of Applied Physiology, 1999)
The energy cost of kayaking per unit distance (Ck, kJ · m-1) was assessed in eight middle- to high-class athletes (three males and five females. Result: The net Ck was a continuous power function of the speed over the entire range of velocities from 2.88 to 4.45 m · s-1: Ck = 0.02 · v2.26 (r = 0.937, n = 32).